2018
DOI: 10.1177/0734282918800748
|View full text |Cite
|
Sign up to set email alerts
|

Perfectionism and Academic Performance in Italian College Students

Abstract: This study analyzed the psychometric properties of the Italian translation of both the Short Almost Perfect Scale (SAPS) and the Short Multidimensional Perfectionism Scale (SMPS), and the academic implications of perfectionism on 414 Italian college students aged between 18 and 58 years. Results revealed some limitations with the SAPS factor structure that, once addressed, yielded scores with good internal consistency and convergent validity. The SMPS had adequate psychometric properties. Higher perfectionisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 31 publications
2
19
0
Order By: Relevance
“…Moreover, another methodological issue concerns the instrument we used for evaluating PS and PC, namely, the Short Almost-Perfect Scale (SAPS) (90). The Italian version (92) does not have fully satisfactory psychometric properties. Hence, the results for perfectionism should be evaluated while taking into account this methodological problem, and we suggest that future studies should analyze the role of PS and PC on studyholism by means of another instrument in order to compare the results with those that we found using the SAPS.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Moreover, another methodological issue concerns the instrument we used for evaluating PS and PC, namely, the Short Almost-Perfect Scale (SAPS) (90). The Italian version (92) does not have fully satisfactory psychometric properties. Hence, the results for perfectionism should be evaluated while taking into account this methodological problem, and we suggest that future studies should analyze the role of PS and PC on studyholism by means of another instrument in order to compare the results with those that we found using the SAPS.…”
Section: Discussionmentioning
confidence: 97%
“…The Short Almost Perfect Scale (SAPS) is an eight-item self-report instrument that allows evaluating both PS (standards scale) and PC (discrepancy scale). It is the short form of the Almost Perfect Scale—Revised (APS-R) (91). The participants answer on a seven-point Likert scale ranging from 1 ( strongly disagree ) to 7 ( strongly agree ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, as invariance has not been substantially examined, it is hard to tell whether there are differences on the endorsement of perfectionism over different countries or whether this construct is understood in different ways by different groups. For instance, why is the factor structure of the SAPS different in China (Wang et al, 2007) and South Korea (Park, 2009), but relatively similar in Italy and the USA (Loscalzo et al, 2018)? We argue that more studies need to examine the invariance of the SAPS so that a better picture on why partial invariance has been found for some studies (Rice et al, 2018), but different structures have been reported for others.…”
Section: Measurement Invariancementioning
confidence: 99%
“…For instance, why is the factor structure of the SAPS different in China (Wang et al, 2007) and South Korea (Park, 2009), but relatively similar in Italy and the USA (Loscalzo et al, 2018)? We argue that more studies need to examine the invariance of the SAPS so that a better picture on why partial invariance has been found for some studies (Rice et al, 2018), but different structures have been reported for others. In the present study, we contribute to this debate by presenting evidence of full metric and partial scalar invariance between an individualistic and developed country (the US) and a collectivistic and developing country (Brazil).…”
Section: Measurement Invariancementioning
confidence: 99%